Desinfecção de efluente anaeróbio com o uso de ozônio/cloro - da Silva, Gustavo Henrique Ribeiro [UNESP]; Daniel, Luiz Antonio (FapUNIFESP (SciELO), 2015)
The main purpose of this research was to study the oxidation process, the coliform inactivation effectiveness, and the formation of ozone disinfection byproducts, which were associated with disinfection of the anaerobic sanitary wastewater effluent from a UASB reactor. Such event was performed with ozone applied at doses of 5.0 mg.O3.L-1+ 10 mg.Cl2.L-1 (essay 1); 8.0 mg.O3.L-1 + 20 mg.Cl2.L-1 (essay 2), and 10.0 mg.O3.L-1 + 30 mg.Cl2.L-1 (essay 3). The wastewater used in this research was generated at the Wastewater Treatment Plant of Universidade de São Paulo, in Brazil. The total mean decreases of the chemical oxygen demand for ozonized/ chlorinated effluents were 9, 32 and 37% for assays 1, 2 and 3 respectively. The total coliform inactivation varied from >5,7 to 6,4 log10and >5.8 to >6.0 log10 for Escherichia coli. The formation of aldehydes did not suffer any significant changes (p=0.05) for dosages and contact times applied after ozonation/chlorination assays.
Anaerobic effluent disinfection using ozone/chlorine
Keywords: Anaerobic wastewater; Byproducts; Chlorine; Disinfection; Municipal effluent; Ozone